Hormonal responses to 100 km cross-country skiing during 2 days - Väänänen, I.; Vasankari, T.; Mantysaari, M.; Vihko, V. (The Journal of Sports Medicine and Physical Fitness, 2004)
AIM: The purposes of this study were to investigate the resting levels and the acute hormonal responses of serum testosterone and cortisol, and with time-resolved immunofluorometric assay of luteinising hormone (LH) and follicle stimulating hormone (FSH), to daily repeated prolonged skiing. METHODS: Quasi-experimental design: short-term follow-up, (reversal) field trial to investigate the daily responses of blood hormones to repeated 50 km skiing during 2 days in men. Participants: 10 physically active men (34.8+/-9.7 y, 1.82+/-0.05 m, 76.1+/-6.6 kg, BMI: 23.0+/-1.5 kg.m(-2)) participating in the Finlandia Ski Race, covering a total distance of 100 km during 2 days. Measures: venous blood samples were obtained before and after skiing, and after 1 week's recovery, to determine the concentrations of testosterone, LH, FSH and cortisol in the blood. RESULTS: Testosterone was reduced by over 20 % after both days (p=0.016 and 0.002, respectively). LH decreased after the 1( st) race by 37 % and after the 2nd race by 44 % (p=0.028, both). FSH secretion was stable and cortisol increased 2.2- and 2.6-fold after the races (p<0.001). CONCLUSIONS: The participants in the 2 days' prolonged skiing exercise went through a period of heavy physical stress. They showed changes in their serum testosterone, LH and cortisol concentrations, which, with the exception of the FSH secretion, alter the acute responses of both the adrenal cortex and the hypothalamus-pituitary-testicular axis. When training or competition programmes are planned it should taken into consideration that daily repeated high intensity prolonged skiing without a recovery day may cause hormonal overreaching.